2019
DOI: 10.1042/cs20190351
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction is associated with long-term cognitive impairment in an animal sepsis model

Abstract: Background: Several different mechanisms have been proposed to explain long-term cognitive impairment in sepsis survivors. The role of persisting mitochondrial dysfunction is not known. We thus sought to determine whether stimulation of mitochondrial dynamics improves mitochondrial function and long-term cognitive impairment in an experimental model of sepsis. Methods: Sepsis was induced in adult Wistar rats by cecal ligation and perforation (CLP). Animals received intracerebroventricular inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 54 publications
2
23
0
Order By: Relevance
“…Cognitive impairment was found in 25% of sepsis patients at 1 year after hospital discharge [28], and in about 70% at 1 year after ICU discharge [29]. Consistent with our results, animal studies using a CLP model reported cognitive and emotional dysfunction at day 10 after surgery [30,31]. A series of behavioral tests were carried out in our study, and it was noteworthy that the QX1 formula significantly reduced overall hippocampus-regulated learning and memory impairment detected by MWM and NORT, frontal cortex-regulated anxiety-like behaviors detected by OPT and EPM, and increased exploratory activity revealed by NORT and OFT, comprehensively demonstrated the neuroprotective effects of QX1 formula on behavior changes.…”
Section: Discussionsupporting
confidence: 88%
“…Cognitive impairment was found in 25% of sepsis patients at 1 year after hospital discharge [28], and in about 70% at 1 year after ICU discharge [29]. Consistent with our results, animal studies using a CLP model reported cognitive and emotional dysfunction at day 10 after surgery [30,31]. A series of behavioral tests were carried out in our study, and it was noteworthy that the QX1 formula significantly reduced overall hippocampus-regulated learning and memory impairment detected by MWM and NORT, frontal cortex-regulated anxiety-like behaviors detected by OPT and EPM, and increased exploratory activity revealed by NORT and OFT, comprehensively demonstrated the neuroprotective effects of QX1 formula on behavior changes.…”
Section: Discussionsupporting
confidence: 88%
“…Sepsis survivors have a reduced hippocampal volume [49] and evidence of blood brain barrier (BBB) breakdown, as detected using magnetic resonance imaging (MRI) [ 50 ]. Murine sepsis survivors have increased rates of apoptosis in hippocampal neurons, [51] increased BBB permeability, [52] and ATP depletion [ 53 ]. The occurrence of delirium in sepsis is strongly associated with long-term cognitive issues [ 54 ].…”
Section: Cognitive Dysfunctionmentioning
confidence: 99%
“…Additionally, cerebral ischemia due to hypotension, hypoxia, and microvascular occlusion due to disseminated intravascular coagulation can cause damage, with one in three sepsis patients having (multiple) cerebral infarctions [ 62 ]. Glucose and oxygen deprivation from these infarctions leads to mitochondrial dysfunction and oxidative damage, [63] which results in neuronal apoptosis and cognitive dysfunction in septic rats [ 53 ]. Inducing mitochondrial biogenesis to increase mitochondrial mass improves cerebral ATP levels and cognition [ 53 ].…”
Section: Cognitive Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial dysfunction is a feature of many pathologies, including sepsis [8][9][10]. Recent studies have shown that mitochondrial respiration was acutely decreased in peripheral blood mononuclear cells in pediatric sepsis [11].…”
Section: Introductionmentioning
confidence: 99%